Penguatan Kapasitas Masyarakat dalam Pengolahan Limbah Rumah Tangga Menjadi Pupuk Organik Cair - Julaiha Julaiha; Miza Sasmita; Lailatussaadah Lailatussaadah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2025)
Household waste management remains an environmental challenge at the community level, particularly due to limited knowledge and skills in productively utilizing organic waste. This community service program aims to enhance public awareness and capacity in processing household waste into liquid organic fertilizer through a community development approach. The program was implemented through a series of activities, including educational outreach, demonstration-based training, and continuous assistance for the residents of Gampong Tanjung Deah. The educational sessions focused on increasing participants’ understanding of the environmental impacts of household waste and the benefits of liquid organic fertilizer. At the same time, the training activities emphasized hands-on practice in producing fertilizer from household organic waste. The results indicate an improvement in community knowledge and technical skills related to the processing of organic waste into liquid organic fertilizer. Participants demonstrated positive responses and active engagement throughout the training process, along with a willingness to apply the acquired techniques independently in their daily lives. The use of liquid organic fertilizer has the potential to reduce environmental pollution, improve soil fertility, and decrease reliance on chemical fertilizers. Overall, this community service activity demonstrates that integrating educational outreach, practical training, and community-based assistance is an effective strategy for promoting sustainable household waste management. This approach not only produces liquid organic fertilizer but also fosters environmental awareness, practical skills, and community self-reliance.